(untitled) (Research, Society and Development, 2026)
Gyrification, or cortical folding, is a fundamental process of brain development, characterized by the formation of gyri and sulci that expand the cortical surface and enable increased cognitive capacity. In parallel, the vascular network responsible for the irrigation and drainage of the cortical mantle is established, whose organization follows the morphological complexity of the cortex. Thus, this study aimed to analyze the patterns of cortical formation and their correlation with the morphology and mechanism of cerebral vascularization. A systematized and narrative review of the literature was carried out in databases (SciELO, LILACS/BIREME, PubMed/MEDLINE and Elsevier), complemented by classical works of Anatomy and Neuroanatomy. The data obtained through morphological, descriptive, and functional analysis demonstrate that the gyrification process follows a relatively consistent pattern in regions such as the frontal, parietal, temporal, insular, and occipital lobes, reflecting specific functional specializations. Furthermore, the concomitant formation of the vascular network reveals a stratified arrangement, adapted to regional metabolic demands, with greater density in areas of high functional activity. The interdependence between cortical folding and vascularization was also evidenced, ensuring balance between neuronal growth and energy supply. Alterations in these processes are related to conditions such as polymicrogyria, schizophrenia, and autism, while their evolution in higher primates supported the emergence of complex cognitive functions. It is concluded that the integrated understanding of gyrification and cerebral irrigation expands the knowledge of the anatomical and functional bases of the cortex, with relevant implications for neuroscience, clinical practice, and human evolution.